Depressive symptoms and CSF Alzheimer's disease biomarkers in relation to clinical symptom onset of mild cognitive impairment - Chan, Carol K. (Alzheimers Dement (Amst), 2020)
INTRODUCTION: We sought to examine whether depressive symptoms and level of Alzheimer's disease (AD) pathology are independently or interactively associated with the risk of progression to mild cognitive impairment (MCI). METHODS: The study included a total of 216 participants from the Biomarkers for Older Controls at Risk for Alzheimer's Disease study, a cohort of individuals who were cognitively normal at baseline (mean age = 57) and followed for more than 20 years (mean = 12.7 years), who had baseline Hamilton Depression Scale (HAM‐D) scores and cerebrospinal fluid (CSF) amyloid beta (Aβ)(1‐42) , t‐tau, and p‐tau measures available. RESULTS: Cox regression demonstrated that baseline HAM‐D and CSF AD biomarkers were both associated with time to onset of MCI. There was an interaction between HAM‐D scores and markers of AD pathology, in which depression was associated with time of onset in participants with low levels of AD pathology (hazard ratio = 0.64; 95% confidence interval = 0.43–0.95; P= .026). DISCUSSION: The effect of depressive symptoms on progression to clinical symptoms of MCI may be most evident among individuals with low levels of AD pathology.